Comparative evaluation of macro- and microscopic changes in rabbit, cattle, and pig auricular cartilage following exhumation after different postmortem intervals - Gorza, Leonardo Lima; Oliveira, Ellen Cristina de; Abreu, Douglas Marinho; Ocarino, Natália de Melo; Figueiredo, Tadeu Chaves de; Lana, Ângela Maria Quintão; Bertassoli, Bruno Machado; Reis, Amanda Maria Sena; Serakides, Rogéria (Brazilian Journal of Veterinary Pathology, 2024)
The study evaluated and compared macro- and microscopic changes in the auricular cartilage of rabbits, cattle, and pigs following exhumation at different postmortem intervals (PMI). Eight samples corresponding to 0, 5, 10, 15, 20, 25, 30, and 150 days after exhumation were obtained from all rabbit ears, and twelve samples corresponding to 0, 5, 10, 15, 20, 25, 30, 35, 40, 50, 60, and 150 days after exhumation were obtained from all cattle and pig ears. The weight loss of the rabbit ear samples remained higher than that of the cattle and pig ear samples at all PMIs. At 60 days, the average weight loss of cattle and pig ear samples did not differ significantly (p>0.05). The loss of area of the samples was similar among the three species at most PMIs (p>0.05). At 150 days, all cattle samples were completely decomposed, unlike the pig and rabbit samples. Microscopic analysis of the cartilage tinctorial affinity and loss of chondrocyte nuclei and tissue architecture demonstrated the worsening of postmortem changes over time, regardless of the animal species. Colonization by fungi and bacteria occurred earlier in the cattle and pig samples. The correlation of time with sample weight loss and cartilage thickness was strong, indicating the potential of these variables as parameters for PMI estimation. Therefore, postmortem examination of auricular cartilage can be used to estimate PMI.